Silicon nitride ceramic substrate and preparation method thereof

By introducing carbon nanotubes and rare earth fluoride into the silicon nitride ceramic substrate and applying a directional magnetic field during the casting process, the problem of insufficient thermal conductivity and mechanical strength of the silicon nitride ceramic substrate is solved, and higher performance and safer production processes are achieved.

CN119350042BActive Publication Date: 2025-03-11HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411908918.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing silicon nitride ceramic substrates have problems such as insufficient thermal conductivity and mechanical strength in the molding process, and the water-based casting molding process has problems such as poor slurry dispersion effect and prone to cracking in the sintering of the blank.

Method used

A composite material consisting of silicon nitride, carbon nanotubes, sintering aids, binders and other additives is used to prepare a silicon nitride ceramic substrate through ball milling and casting molding, and a directional magnetic field is applied during casting molding to improve the orientation arrangement of the carbon nanotubes.

Benefits of technology

The mechanical strength and thermal conductivity of the silicon nitride ceramic substrate are improved, and the use of organic solvents is reduced through the water-based casting molding process, which improves the safety and environmental protection of production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350042B_ABST
    Figure CN119350042B_ABST
Patent Text Reader

Abstract

The invention relates to the field of ceramic materials, in particular to a silicon nitride ceramic substrate and a preparation method thereof. The silicon nitride ceramic substrate is prepared from the following raw materials in parts by weight: 80-100 parts of silicon nitride, 5-10 parts of carbon nanotubes, 5-10 parts of sintering aids, 5-10 parts of binders, 1-3 parts of dibutyl phthalate, 1-3 parts of ammonium polyacrylate, and 50-70 parts of deionized water. The binder is sulfonic acid group-modified polyvinyl alcohol, and rare earth fluoride and nano iron particles are deposited on the surface of the carbon nanotubes. The silicon nitride ceramic substrate prepared by the invention has high mechanical strength and excellent thermal conductivity, and adopts a water-based tape casting molding process, thereby avoiding the use of a large amount of organic solvents, and having fewer safety and environmental protection problems in a large-scale production process, and can meet the application requirements of highly integrated circuit packaging substrate materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic materials, in particular to a silicon nitride ceramic substrate and a preparation method thereof. Background Art

[0002] An electronic integrated circuit is a microstructure that integrates the required transistors, resistors, capacitors, inductors and other electronic components on a packaging substrate to form a required circuit function. Therefore, the packaging substrate plays an important role. It is not only a hub for absorbing chip heat to achieve heat transfer with the outside world, but also a barrier to protect internal chips and other devices from damage. With the increase in integration, heat dissipation and reliability issues are becoming increasingly prominent. The key lies in the need to further develop and improve the heat dissipation and reliability of the packaging substrate.

[0003] For packaging substrate materials of highly integrated circuits, in addition to excellent thermal conductivity to ensure that heat can be quickly dissipated, they must also have a thermal expansion coefficient that matches that of semiconductor materials and higher strength and hardness to resist external physical impacts. Silicon nitride ceramics, as structural ceramics with the best comprehensive performance, are often used to make ceramic substrates. Their performance is affected by many factors, including ceramic powders, additives, molding processes, and sintering processes.

[0004] The molding process is the key link in the preparation of silicon nitride ceramic materials. The ceramic green sheets prepared by the silicon nitride organic tape casting system have fewer defects, high strength and good toughness, but require the use of a large amount of organic solvents, which poses many problems such as safety and environmental protection. The water-based tape casting method for preparing silicon nitride ceramic materials has problems such as poor slurry dispersion and easy cracking of the green body during sintering, resulting in less than ideal mechanical strength and thermal conductivity of the prepared silicon nitride ceramic materials. Summary of the invention

[0005] Purpose of the invention: In view of the above technical problems, the present invention proposes a silicon nitride ceramic substrate and a preparation method thereof.

[0006] The technical solutions adopted are as follows:

[0007] A silicon nitride ceramic substrate is prepared from the following raw materials in parts by weight:

[0008] 80-100 parts of silicon nitride, 5-10 parts of carbon nanotubes, 5-10 parts of sintering aid, 5-10 parts of binder, 1-3 parts of dibutyl phthalate, 1-3 parts of ammonium polyacrylate, and 50-70 parts of deionized water;

[0009] The binder is sulfonic acid modified polyvinyl alcohol, and rare earth fluoride and nano iron particles are deposited on the surface of the carbon nanotubes;

[0010] The preparation method of the carbon nanotubes is as follows:

[0011] The rare earth fluoride is dissolved in a mixed acid solution composed of concentrated sulfuric acid and concentrated nitric acid, and then multi-walled carbon nanotubes are added. The temperature is raised to reflux for reaction for 1-5 hours under ultrasonic action. After the reaction is completed, the precipitate is collected by centrifugation, washed with deionized water until neutral, and then dried. The carbonyl iron is then coated by vapor deposition, and finally heated to decompose the carbonyl iron.

[0012] The sulfonic acid modified polyvinyl alcohol is 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol;

[0013] The preparation method of the 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol is as follows:

[0014] Under nitrogen protection, polyvinyl alcohol and 2-acrylamido-2-methylpropanesulfonic acid in a mass ratio of 10-50:1 are dissolved in deionized water, and potassium persulfate is added. The reaction is carried out in a water bath at 60-80°C for 5-10 hours. A portion of the deionized water is removed by pressure distillation, and anhydrous ethanol is added dropwise to obtain a white precipitate. The white precipitate is filtered out and dried.

[0015] The sintering aid is composed of magnesium oxide and rare earth oxide;

[0016] The mass ratio of the magnesium oxide to the rare earth oxide is 5-10:1-5.

[0017] Furthermore, the rare earth fluoride is any one of neodymium fluoride, europium fluoride, gadolinium fluoride, and cerium fluoride, or a combination of any two or more thereof.

[0018] Furthermore, the mass ratio of the concentrated sulfuric acid to the concentrated nitric acid is 1-5:1-5.

[0019] Furthermore, the mass ratio of the rare earth fluoride to the multi-walled carbon nanotube is 1:5-15.

[0020] Furthermore, the rare earth oxide is any one of lanthanum oxide, cerium oxide, and samarium oxide, or a combination of any two or more thereof.

[0021] The present invention also provides a method for preparing a silicon nitride ceramic substrate:

[0022] Silicon nitride, carbon nanotubes, sintering aid, ammonium polyacrylate and deionized water are mixed and ball-milled, then a binder and dibutyl phthalate are added, and the ball-milling is continued to obtain a slurry. The slurry is vacuum defoamed and then tape-cast to obtain a sheet. After the sheet is dried and degreased, it is placed in a gas pressure sintering furnace and sintered at 1600-1800°C and 1-2MPa nitrogen pressure for 1-5 hours.

[0023] Furthermore, an aligning magnetic field is applied during tape casting.

[0024] Furthermore, the direction of the oriented magnetic field is consistent with the running direction of the casting machine.

[0025] Furthermore, the intensity of the directional magnetic field is 1-5T.

[0026] Beneficial effects of the present invention:

[0027] The present invention provides a silicon nitride ceramic substrate. Carbon nanotubes are refluxed in a mixed acid solution containing rare earth fluorides. Negatively charged functional groups are introduced on the surface of the carbon nanotubes. These functional groups can adsorb rare earth fluorides. At the same time, strong acid can open both ends of the carbon nanotubes. Rare earth fluorides enter the cavities of the carbon nanotubes through capillary action. On the one hand, the dispersibility of the carbon nanotubes in the ceramic matrix is ​​improved. On the other hand, the rare earth fluorides, as non-oxide sintering aids, can cooperate with the carbon nanotubes to reduce the oxygen content in the silicon nitride sintering system, hinder the formation of lattice oxygen in the dissolution and precipitation process, and promote the development of large-sized β-Si3N4 grains.

[0028] Nano-iron obtained by decomposing carbonyl iron can guide carbon nanotubes to overcome the viscous resistance of the slurry within a certain range under the action of an external magnetic field, and realize directional arrangement along the magnetic flux lines, thereby being more conducive to forming a complete three-dimensional heat conduction path and improving the performance of silicon nitride ceramic substrates.

[0029] There are a large number of sulfonic acid functional groups in the 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol molecules, which can make the surface of ceramic particles negatively charged, achieve uniform dispersion of the slurry through steric hindrance mechanism and electrostatic repulsion mechanism, and build a three-dimensional network between ceramic particles, providing the necessary strength and toughness for the ceramic cast film, ensuring that it maintains a stable shape during processing, and helping to obtain a silicon nitride ceramic substrate with better mechanical properties and thermal conductivity;

[0030] After testing, the silicon nitride ceramic substrate prepared by the present invention has high mechanical strength and excellent thermal conductivity, and adopts a water-based tape-casting process, which avoids the use of a large amount of organic solvents. There are fewer safety and environmental problems in the large-scale production process, and it can meet the application requirements of highly integrated circuit packaging substrate materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM image of the cross section of the silicon nitride ceramic substrate prepared in Example 1. DETAILED DESCRIPTION

[0032] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0033] Embodiment 1:

[0034] A silicon nitride ceramic substrate is prepared from the following raw materials in parts by weight:

[0035] 95 parts of silicon nitride, 8 parts of carbon nanotubes, 6 parts of magnesium oxide, 2 parts of lanthanum oxide, 8 parts of binder, 2 parts of dibutyl phthalate, 1.5 parts of ammonium polyacrylate, and 60 parts of deionized water.

[0036] The preparation method of carbon nanotubes is as follows:

[0037] Dissolve 1g of neodymium fluoride in a mixed acid solution composed of 80ml of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 3:1, then add 10g of multi-walled carbon nanotubes, heat to reflux reaction for 2h under ultrasonic action, collect the precipitate by centrifugation after the reaction, wash it with deionized water until it is neutral, and then dry it to obtain neodymium fluoride modified carbon nanotubes, then place the neodymium fluoride modified carbon nanotubes in the reaction tube of the vapor deposition equipment, and pass gaseous carbonyl iron into the reaction tube at a flow rate of 50sccm. The vapor deposition time is 30min. After the end, take out the product, place it in a muffle furnace and heat it to 200℃, and keep it warm for 20h to decompose the carbonyl iron into nano iron particles.

[0038] The binder is 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol, and the preparation method is as follows:

[0039] Under nitrogen protection, 50g of polyvinyl alcohol and 20g of 2-acrylamido-2-methylpropanesulfonic acid were dissolved in 1000ml of deionized water, and 0.1g of potassium persulfate was added. The mixture was reacted in a water bath at 80°C for 10h. After 900ml of deionized water was removed by pressure distillation, 1000ml of anhydrous ethanol was added dropwise to obtain a white precipitate. The white precipitate was filtered out and dried.

[0040] The preparation method of the above silicon nitride ceramic substrate is as follows:

[0041] Silicon nitride, carbon nanotubes, magnesium oxide, lanthanum oxide, ammonium polyacrylate and deionized water are added to a ball mill, mixed and ball-milled on a planetary ball mill for 10 hours, then a binder and dibutyl phthalate are added, and the ball milling is continued for 5 hours to obtain a slurry. The slurry is vacuum defoamed and then tape-casted in a tape casting machine to obtain a sheet. During the tape casting, a directional magnetic field is applied to the tape casting machine with a magnetic field intensity of 2T. The direction of the magnetic field is consistent with the running direction of the tape casting machine. The sheet is dried at 80°C for 10 hours and then degreased at 650°C for 2 hours. Finally, the sheet is placed in a gas pressure sintering furnace and sintered at 1700°C and 2MPa nitrogen pressure for 2 hours.

[0042] Embodiment 2:

[0043] A silicon nitride ceramic substrate is prepared from the following raw materials in parts by weight:

[0044] 100 parts of silicon nitride, 5 parts of carbon nanotubes, 6 parts of magnesium oxide, 2 parts of lanthanum oxide, 10 parts of binder, 1 part of dibutyl phthalate, 3 parts of ammonium polyacrylate, and 70 parts of deionized water.

[0045] Wherein, the preparation method of carbon nanotubes is the same as that of Example 1;

[0046] The binder is 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol, and the preparation method is the same as that of Example 1;

[0047] The preparation method of the above silicon nitride ceramic substrate is as follows:

[0048] Silicon nitride, carbon nanotubes, magnesium oxide, lanthanum oxide, ammonium polyacrylate and deionized water are added to a ball mill, mixed and ball-milled on a planetary ball mill for 10 hours, then a binder and dibutyl phthalate are added, and the ball milling is continued for 5 hours to obtain a slurry. The slurry is vacuum defoamed and then tape-casted in a tape casting machine to obtain a sheet. During the tape casting, a directional magnetic field is applied to the tape casting machine with a magnetic field intensity of 2T. The direction of the magnetic field is consistent with the running direction of the tape casting machine. The sheet is dried at 80°C for 10 hours and then degreased at 650°C for 2 hours. Finally, the sheet is placed in a gas pressure sintering furnace and sintered at 1700°C and 2MPa nitrogen pressure for 2 hours.

[0049] Embodiment 3:

[0050] A silicon nitride ceramic substrate is prepared from the following raw materials in parts by weight:

[0051] 100 parts of silicon nitride, 10 parts of carbon nanotubes, 6 parts of magnesium oxide, 2 parts of lanthanum oxide, 10 parts of binder, 3 parts of dibutyl phthalate, 3 parts of ammonium polyacrylate, and 70 parts of deionized water.

[0052] Wherein, the preparation method of carbon nanotubes is the same as that of Example 1;

[0053] The binder is 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol, and the preparation method is the same as that of Example 1;

[0054] The preparation method of the above silicon nitride ceramic substrate is as follows:

[0055] Silicon nitride, carbon nanotubes, magnesium oxide, lanthanum oxide, ammonium polyacrylate and deionized water are added to a ball mill, mixed and ball-milled on a planetary ball mill for 10 hours, then a binder and dibutyl phthalate are added, and the ball milling is continued for 5 hours to obtain a slurry. The slurry is vacuum defoamed and then tape-casted in a tape casting machine to obtain a sheet. During the tape casting, a directional magnetic field is applied to the tape casting machine with a magnetic field intensity of 2T. The direction of the magnetic field is consistent with the running direction of the tape casting machine. The sheet is dried at 80°C for 10 hours and then degreased at 650°C for 2 hours. Finally, the sheet is placed in a gas pressure sintering furnace and sintered at 1700°C and 2MPa nitrogen pressure for 2 hours.

[0056] Embodiment 4:

[0057] A silicon nitride ceramic substrate is prepared from the following raw materials in parts by weight:

[0058] 80 parts of silicon nitride, 5 parts of carbon nanotubes, 6 parts of magnesium oxide, 2 parts of lanthanum oxide, 6 parts of binder, 1.5 parts of dibutyl phthalate, 1.5 parts of ammonium polyacrylate, and 70 parts of deionized water.

[0059] Wherein, the preparation method of carbon nanotubes is the same as that of Example 1;

[0060] The binder is 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol, and the preparation method is the same as that of Example 1;

[0061] The preparation method of the above silicon nitride ceramic substrate is as follows:

[0062] Silicon nitride, carbon nanotubes, magnesium oxide, lanthanum oxide, ammonium polyacrylate and deionized water are added to a ball mill, mixed and ball-milled on a planetary ball mill for 10 hours, then a binder and dibutyl phthalate are added, and the ball milling is continued for 5 hours to obtain a slurry. The slurry is vacuum defoamed and then tape-casted in a tape casting machine to obtain a sheet. During the tape casting, a directional magnetic field is applied to the tape casting machine with a magnetic field intensity of 2T. The direction of the magnetic field is consistent with the running direction of the tape casting machine. The sheet is dried at 80°C for 10 hours and then degreased at 650°C for 2 hours. Finally, the sheet is placed in a gas pressure sintering furnace and sintered at 1700°C and 2MPa nitrogen pressure for 2 hours.

[0063] Comparative Example 1:

[0064] The method is basically the same as Example 1, except that commercially available multi-walled carbon nanotubes are used instead of homemade carbon nanotubes.

[0065] Comparative Example 2:

[0066] The method is basically the same as Example 1, except that the self-made carbon nanotubes are replaced by multi-walled carbon nanotubes modified with neodymium fluoride.

[0067] The preparation method of NdF-modified multi-walled carbon nanotubes is as follows:

[0068] 1g of neodymium fluoride was dissolved in 80ml of a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 3:1, and then 10g of multi-walled carbon nanotubes was added. The temperature was raised to reflux reaction for 2h under ultrasonic action. After the reaction, the precipitate was collected by centrifugation, washed thoroughly with deionized water until neutral, and then dried to obtain neodymium fluoride modified multi-walled carbon nanotubes.

[0069] Comparative Example 3:

[0070] It is basically the same as Example 1, except that no directional magnetic field is applied during the tape casting process.

[0071] Comparative Example 4:

[0072] The method is basically the same as Example 1, except that polyvinyl alcohol is used as the binder instead of 2-acrylamide-2-methylpropanesulfonic acid graft-modified polyvinyl alcohol.

[0073] Performance test: The silicon nitride ceramic substrates in Examples 1-4 and Comparative Examples 1-4 were made into samples for performance testing;

[0074] The three-point bending strength of the sample was tested using a SANS-CMT5104A universal testing machine. The sample size was 3 mm × 4 mm × 20 mm and the loading rate was 0.5 mm min. -1 The thermal diffusivity of the sample was measured by LFA-457 laser thermal conductivity analyzer, and its thermal conductivity (λ: W·m -1 ·K -1 ) is calculated by the following formula:

[0075] ;

[0076] Where: α is the thermal diffusion coefficient, c p is the isobaric specific heat capacity, ρ is the bulk density of the sample;

[0077] The test results are shown in Table 1 below:

[0078] ;

[0079] It can be seen from Table 1 above that the silicon nitride ceramic substrate prepared by the present invention has high mechanical strength and excellent thermal conductivity;

[0080] Multi-walled carbon nanotubes not only improve the mechanical properties of silicon nitride ceramic substrates, but also form a heat conduction path inside the silicon nitride ceramic substrate, so that heat can be more effectively transferred during the heat conduction process, thereby improving the thermal conductivity of the silicon nitride ceramic substrate. However, directly adding multi-walled carbon nanotubes not only easily agglomerates, but also arranges in a disordered manner, which has limited improvement on the performance of the silicon nitride ceramic substrate. Therefore, compared with Example 1, Comparative Example 1 has significant differences in both mechanical properties and thermal conductivity.

[0081] The agglomeration degree of the multi-walled carbon nanotubes modified by neodymium fluoride is reduced, so the mechanical properties and thermal conductivity of Comparative Example 2 are improved compared with Comparative Example 1, but they are still disorderly arranged inside the silicon nitride ceramic substrate, so the mechanical properties and thermal conductivity of the silicon nitride ceramic substrate in Comparative Example 2 are still not as good as those in Example 1;

[0082] When a directional magnetic field is applied to the casting machine, the carbon nanotubes can overcome the viscous resistance of the slurry within a certain range under the condition of the external magnetic field, and realize directional arrangement along the magnetic flux lines, thereby being more conducive to forming a complete three-dimensional heat conduction path, thereby realizing the improvement of the performance of the silicon nitride ceramic substrate, which can be confirmed by the data comparison of Example 1 and Comparative Example 3;

[0083] A large number of sulfonic acid functional groups exist in the 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol molecules, which can make the surface of the ceramic particles negatively charged, achieve uniform dispersion of the slurry through a steric hindrance mechanism and an electrostatic repulsion mechanism, and construct a three-dimensional network between the ceramic particles, thereby providing the necessary strength and toughness for the ceramic cast film, ensuring that it maintains a stable shape during processing, and helping to obtain a silicon nitride ceramic substrate with better mechanical properties and thermal conductivity. By comparing the data of Example 1 and Comparative Example 4, it can be seen that the performance of the silicon nitride ceramic substrate prepared by using the 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol as a binder is better than that of the silicon nitride ceramic substrate prepared by using polyvinyl alcohol as a binder.

[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon nitride ceramic substrate, characterized in that: It is prepared from the following raw materials in parts by weight: 80-100 parts of silicon nitride, 5-10 parts of carbon nanotubes, 5-10 parts of sintering aid, 5-10 parts of binder, 1-3 parts of dibutyl phthalate, 1-3 parts of ammonium polyacrylate, and 50-70 parts of deionized water; The binder is sulfonic acid modified polyvinyl alcohol, and rare earth fluoride and nano iron particles are deposited on the surface of the carbon nanotubes; The preparation method of the carbon nanotubes is as follows: The rare earth fluoride is dissolved in a mixed acid solution composed of concentrated sulfuric acid and concentrated nitric acid, and then multi-walled carbon nanotubes are added. The temperature is raised to reflux for reaction for 1-5 hours under ultrasonic action. After the reaction is completed, the precipitate is collected by centrifugation, washed with deionized water until neutral, and then dried. The carbonyl iron is then coated by vapor deposition, and finally heated to decompose the carbonyl iron. The sulfonic acid modified polyvinyl alcohol is 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol; The preparation method of the 2-acrylamide-2-methylpropanesulfonic acid grafted modified polyvinyl alcohol is as follows: Under nitrogen protection, polyvinyl alcohol and 2-acrylamido-2-methylpropanesulfonic acid in a mass ratio of 10-50:1 are dissolved in deionized water, and potassium persulfate is added. The reaction is carried out in a water bath at 60-80°C for 5-10 hours. A portion of the deionized water is removed by pressure distillation, and anhydrous ethanol is added dropwise to obtain a white precipitate. The white precipitate is filtered out and dried. The sintering aid is composed of magnesium oxide and rare earth oxide; The mass ratio of magnesium oxide to rare earth oxide is 5-10:1-5; The mass ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:

1.

2. The silicon nitride ceramic substrate according to claim 1, characterized in that: The rare earth fluoride is any one of neodymium fluoride, europium fluoride, gadolinium fluoride and cerium fluoride, or a combination of any two or more thereof.

3. The silicon nitride ceramic substrate according to claim 1, characterized in that: The rare earth oxide is any one of lanthanum oxide, cerium oxide and samarium oxide, or a combination of any two or more thereof.

4. A method for preparing a silicon nitride ceramic substrate as claimed in any one of claims 1 to 3, characterized in that: Silicon nitride, carbon nanotubes, sintering aid, ammonium polyacrylate and deionized water are mixed and ball-milled, then a binder and dibutyl phthalate are added, and the ball-milling is continued to obtain a slurry. The slurry is vacuum defoamed and then tape-cast to obtain a sheet. After the sheet is dried and degreased, it is placed in a gas pressure sintering furnace and sintered at 1600-1800°C and 1-2MPa nitrogen pressure for 1-5 hours.

5. The method for preparing a silicon nitride ceramic substrate according to claim 4, characterized in that: An oriented magnetic field is applied during tape casting.

Citation Information

Patent Citations

  • Dense and homogeneous ceramic material consisting of carbon / silicon nitride nanotubes, production method and applications thereof

    ES2326018A1

  • Electroconductive silicon nitride sintered body and its manufacturing process

    JP2008069036A